1998
DOI: 10.1159/000044987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrauterine Growth Retardation on the Clinical Course and Prognosis of IgA Glomerulonephritis in Children

Abstract: Intrauterine growth retardation (IUGR) resulting in a reduced number of nephrons is one of the nonimmune mechanisms that have been recently proposed as contributing to the progression of renal diseases. The purpose of our study was to determine whether IUGR has any effect on the clinical course and prognosis of IgA glomerulonephritis (IgA GN) in children. Fifty children with biopsy-proven IgA GN, who were followed for at least 3 years, were included. Six of the 50 children (12%) had signs of IUGR at birth, def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 23 publications
2
58
0
3
Order By: Relevance
“…Some studies have suggested that there is substantial variation in the nephron number in normal people without renal diseases (20,21). It is interesting that a low nephron number was shown to be associated with low birth weight, which was also shown to be associated with poor outcome of glomerular diseases, including IgAN (22)(23)(24). The second possibility is an effect of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that there is substantial variation in the nephron number in normal people without renal diseases (20,21). It is interesting that a low nephron number was shown to be associated with low birth weight, which was also shown to be associated with poor outcome of glomerular diseases, including IgAN (22)(23)(24). The second possibility is an effect of aging.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain associations of low BW with such clinical outcomes as albuminuria, low-normal kidney function, and ESRD. [6][7][8][9][10][11][12][13][14][15][16][17]37 However, these are only a few studies, sometimes with a weak design, and the effects found were not strong. Case-control studies showed an OR of 1.5 for ESRD in subjects with BWs less than 2,500 g, but data for BW were missing in half the cases.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The clinical consequences of these alterations were investigated at different levels, and associations were found of IUGR with microalbuminuria, 11,12 faster progression of renal dysfunction in patients with specific kidney diseases, 13,14 and end-stage renal disease (ESRD). 15,16 Because IUGR also was associated with other diseases, such as type 2 diabetes mellitus, it is difficult to disentangle direct from indirect effects of IUGR on advanced renal failure.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital nephron deficits may interact with environmental and genetic factors to generate glomerulosclerosis [35]. In children with nephrotic syndrome [36] or IgA nephropathy [37], those with intrauterine growth retardation had higher blood pressure and more rapidly progressive disease than those of normal birth weight.…”
Section: Discussionmentioning
confidence: 99%